MEDIA APPROACH TO POVERTY ALLEVIATION PROGRAMMES IN CHIKUN LOCAL GOVERNMENT AREA OF KADUNA STATE - Emmanuel Jibb Adams (International Studies Journal)
Poverty is a global phenomenon recognized by United Nations as part of the Sustainable Development Goals (SDG) and the anti-poverty program's initiatives adopted by different governments to tackle this menace and bring poverty to zero level still shows that more are still needed to do in other to actualize and sustain the socio-economic development of the country. This research paper critically evaluates media approach to poverty alleviation in Chikun Local Government Area. Hinged on Development Media Theory findings showed that media play great role in promoting knowledge and national development programmes. Consequently, where there is a communication gap, it is likely to result in an interruption in the attainment of poverty alleviation programmes. The study, recommends that all future anti-poverty programmes of the government must have provision for an adequate budget to utilize the rural media and communication strategies including face-to face and radio to publicize these programmes so that no one among the poor will be excluded.